Dimethyl fumarate abrogates striatal endoplasmic reticulum stress in experimentally induced late-stage Huntington’s disease: Focus on the IRE1α/JNK and PERK/CHOP trajectories - Hassab, Lina Y.; Abbas, Samah S.; Mohammed, Reham A.; Abdallah, Dalaal M. (Frontiers in Pharmacology, 2023)
Dimethyl fumarate (DMF) is FDA approved for relapsing multiple sclerosis and processes neuroprotection in several experimental settings; nonetheless, its impact in combating Huntington’s disease (HD) remains elusive. This study aimed to explore the role of DMF post-treatment on HD-mediated endoplasmic reticulum (ER) stress response in a selective striatal degeneration HD model. Rats, exposed to 3-nitropropionic acid, were either left untreated or post-treated with DMF for 14 days. DMF reduced locomotion deficits in both the open field and beam walk paradigms, boosted the striatal dopamine (DA) content, improved its architecture at the microscopic level and hindered astrogliosis. Mechanistically, DMF limited the activation of two of the ER stress arms in the striatum by reducing p-IRE1α, p-JNK and p-PERK protein expressions, besides the CHOP/GADD153 content. Downstream from both ER stress arms suppression, it inhibited the intrinsic apoptotic pathway as shown by the decrease in Bax and active caspase-3 while raising Bcl-2. DMF also decreased oxidative stress markers indicated by declines in both reactive oxygen species and malondialdehyde while boosting glutathione. Meanwhile, it enhanced p-AKT to activate/phosphorylate mTOR and stimulate the CREB/BDNF/TrkB trajectory which in a positive feedforward loop activates AKT again. DMF also downregulated the expression of miRNA-634, which negatively regulates AKT, to foster the survival kinase activation. Conclusion: This study features a focal novel point on DMF therapeutic ability to reduce HD-motor manifestations via its ability to enhance DA and suppress the IRE1α/JNK and PERK/CHOP/GADD153 hubs to inhibit the mitochondrial apoptotic pathway through activating the AKT/mTOR, BDNF/TrkB/AKT/CREB signaling pathways and abating miRNA-634 and oxidative stress.